Supervisi Dalam Pendidikan - Dhiya Wirdatul Izzah; Agus Gunawan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Education is one of the important pillars in the development of society and the country. To ensure a quality learning experience, educational supervision becomes an inevitable component in the education system. This article outlines various aspects of educational supervision, including the types, techniques, types, and processes involved in the process of supervising and improving educational practice. The approach in this article uses a qualitative approach with literature study data collection techniques. The type of supervision based on the supervisor's work attitude is supervision that is corrective, prefentive, constructive, creative. Educational supervision techniques are carried out individually and in groups. The types of educational supervision that can be used are autocratic, democratic, laisses faire, coercive, and training and guidance. The educational supervision process includes the planning, implementation, evaluation, and follow-up stages.